Homozygous/Compound Heterozygous Triadin Mutations Associated With Autosomal-Recessive Long-QT Syndrome and Pediatric Sudden Cardiac Arrest: Elucidation of the Triadin Knockout Syndrome. Issue 23 (9th June 2015) - Altmann, Helene M.; Tester, David J.; Will, Melissa L.; Middha, Sumit; Evans, Jared M.; Eckloff, Bruce W.; Ackerman, Michael J.
Abstract : Background—: Long-QT syndrome (LQTS) may result in syncope, seizures, or sudden cardiac arrest. Although 16 LQTS-susceptibility genes have been discovered, 20% to 25% of LQTS remains genetically elusive. Methods and Results—: We performed whole-exome sequencing child–parent trio analysis followed by recessive and sporadic inheritance modeling and disease-network candidate analysis gene ranking to identify a novel underlying genetic mechanism for LQTS. Subsequent mutational analysis of the candidate gene was performed with polymerase chain reaction, denaturing high-performance liquid chromatography, and DNA sequencing on a cohort of 33 additional unrelated patients with genetically elusive LQTS. After whole-exome sequencing and variant filtration, a homozygous p.D18fs*13 TRDN -encoded triadin frameshift mutation was discovered in a 10-year-old female patient with LQTS with a QTc of 500 milliseconds who experienced recurrent exertion-induced syncope/cardiac arrest beginning at 1 year of age. Subsequent mutational analysis of TRDN revealed either homozygous or compound heterozygous frameshift mutations in 4 of 33 unrelated cases of LQTS (12%). All 5 TRDN-null patients displayed extensive T-wave inversions in precordial leads V1 through V4, with either persistent or transient QT prolongation and severe disease expression of exercise-induced cardiac arrest in early childhood (⩽3 years of age) and required aggressive therapy. The overall yield of TRDN mutations was significantly greater in patients ⩽10 years of age (5 of 10, 50%) compared with older patients (0 of 24, 0%; P =0.0009). Conclusions—: We identified TRDN as a novel underlying genetic basis for recessively inherited LQTS. All TRDN-null patients had strikingly similar phenotypes. Given the recurrent nature of potential lethal arrhythmias, patients fitting this phenotypic profile should undergo cardiac TRDN genetic testing.